Faktor-Faktor Yang Mempengaruhi Independensi Hakim Di Pengadilan - Nurwandri, Andri; Syam, Nur Fadhilah; Fadhillah, Dimas Ari; Larasari, Suryani; Nurmala, Nurmala; Tambunan, Nani Astuti; Sulina, Sulina (Journal of Educational Research and Humaniora (JERH), 2023)
The purpose of this writing is to contribute ideas to the public regarding the problems of the independence of judges as executors of judicial power, and is a legal instrument for judges in carrying out their function of adjudicating and deciding a case presented to them so that they are free from all interference and/or influence from other power environments, whether from the organ environment. executive power as well as from within the organs of legislative power. This article uses a normative research type, and providing the results of this research suggests that judges in deciding cases in Indonesia still exist to explore and find a sense of justice in society, even with a religious norms approach where it is known that Indonesian society is quite obedient to religious norms.